Estudos quimiotaxonômicos e triagem virtual de diterpenos isolados da família Lamiaceae com potencial atividade antitubercular - Cavalcanti, Andreza Barbosa Silva (2021)
The Lamiaceae family has a cosmopolitan distribution, being composed of a wide variety of secondary metabolites, has more than 290 genera and 7000 species. It is estimated that in Brazil this family is searched for 36 genera and 490 species. Given the great diversity of the Lamiaceae family, the objective of this work was to create a database of diterpenes, carry out auxiliary chemotaxonomic studies in the prospection of diterpenes with specific structural characteristics, as well as virtual screening, selecting the most promising, and finally validate through of the biological activity test. In chapter 2, a database of diterpenes from Lamiaceae was built and with it a chemotaxonomic analysis was performed among the subfamilies of Lamiaceae, using molecular descriptors and self-organizing maps (SOMs). The data collection showed 4115 different diterpenes corresponding to 6386 botanical occurrences, which are distributed in eight subfamilies, 66 genera, 639 different species and 4880 geographic locations were added to SistematX. In all maps obtained, a hit rate of more than 80% was observed, demonstrating a separation of the subfamilies of Lamiaceae, corroborating the morphological and molecular data proposed by Li et al. Therefore, through this chemotaxonomic study, it was possible to predict the location of a diterpene in a subfamily and assist in the search for secondary metabolites with specific structural characteristics, such as compounds with potential biological activity. Chapter 3 presents an in silico evaluation of the labdane diterpene acid, labda-8 (17), 14-dien-9,13-epoxy-12β-hydroxy-19-oic acid, called hyptenol (1), together with five other compounds: erythroxylol B (2), oleanolic acid acetate (3), betulinic acid (4), tormentic acid (5) and ent-3β-acetoxy-kaur-15-en-17-oic acid (6) which are chemical constituents of the aerial parts of Leptohyptis macrostachys. A predictive model was created to determine the susceptibility to the tuberculosis microbacteria, with molecular evaluations, and then in vitro analyzes were performed of secondary metabolites with specific structural characteristics, such as compounds with potential biological activity. The results showed that ent-3β-acetoxy-kaur-15-en-17-oic acid (6) has significant biological activity against Mycobacterium tuberculosis. In chapter 4, the phytochemical analysis of the species Mesosphaerum sidifolium, belonging to the subtribe Hyptidinae, was performed, as well as a virtual screening of the diterpene database of this tribe, selecting the most promising compounds with antitubercular activity against M. tuberculosis. The in silico study showed that of the 68 diterpenes of Hyptidinae analyzed, 48 were likely to have biological activity against M. tuberculosis and, through the biological test, it was found that the diterpenes can be evaluated later as potential antitubercular molecules.